Systematic Literature Review: Sistem Pakar Diagnosis Penyakit Pada Manusia Menggunakan Metode Backward Channing - Alin Lestari; Halim Wijaya; Indrawan; Nanang Selamet Riyadi; Perani Rosyani (Shofanah Media Berkah, 2023)
The purpose of this research is to use the Backward Chaining method in an expert system to find various diseases in humans. An expert system is a system that integrates human knowledge into a computer and is used for diagnosis, interpretation and decision making. The focus of this research is also the immune system, also known as the immune system, because it protects the body from infection and disease. Scientific data relevant to the research objectives were collected, evaluated, and synthesized through the Systematic Literature Review (SLR) method. This study also describes the stages of the research method, such as the search process, inclusion and exclusion criteria, assessing the quality of journals, and data analysis. The results of this study indicate that there are a number of journals that are relevant to the research topic and meet the quality criteria. These journals cover various fields, such as diagnosing kidney disease, diagnosing skin diseases in children, and others. Expert systems with the Back Chaining method have advantages in diagnosing diseases. This research provides in-depth understanding of the diseases studied through the collection of scientifically documented information.